The Development of Instructional Video for Online English Subject at SD Dwijendra Denpasar - Juliari, I.G.A.I.T.; Yuniari, N.M; Sudarmawan, I.P.Y (Universitas Pendidikan Ganesha, 2021)
This study aimed at developing instructional video for online English subject. The research takes place at SD Dwijendra Denpasar. The research design used in this study was R&D method by using ADDIE model. This model have five stages development, namely: analysis, design, development, implementation, and evaluation. The purpose of this research is to develop instructional video for online English subject based on validators’ assessment. This research used validation sheets as research instrument. The validators of this research were two validators of subject matter experts, and one for learning media expert. Based on the analysis of data validation, it found that the highest percentage is for pedagogical aspect. It was about 94% data were categorized valid. Thus, it could be concluded that the instructional video for online English subject is appropriate used as teaching media for the third grade students of SD Dwijendra Denpasar.